Lightweight Opened Hollow Bulb Obturator Using a Precise Positioning Method of Metal Framework in Patients with Partial Maxillectomy: a Case Report: A clinical report - Phan, Hai Hoang; Punyawattananon, Visaluk; Tri, Doan Minh; Chotprasert, Natdhanai; Sipiyaruk, Kawin (Khon Kaen University Dental Journal, 2019)
Successes of using an obturator in rehabilitation for a maxillectomy patient depend on size and location of defect. Large maxillary defects with a few remaining abutments located in a relatively straight line lead to a decrease in support, stability, and retention of prostheses due to unfavorable leverage. To minimize this leverage, weight reduction of a prosthesis should be considered. In this clinical report, a patient with a large hemimaxillectomy defect was rehabilitated with a one-piece opened hollow bulb obturator using a cast metal framework. A special tray with opening access was used for making a functional impression of the defect site to obtain a precise working cast. Afterwards, the cast was modified at the defect site to simulate the contour of normal ridge using a mixture of plaster and pumice in order to properly position the meshwork. These procedures, including the predetermined reduction of acrylic thickness, resulted in a lightweight obturator with improvement of stability, retention, and function.